Complex structure of cytochrome c–cytochrome c oxidase reveals a novel protein–protein interaction mode. (15th December 2016) - Shimada, Satoru; Shinzawa‐Itoh, Kyoko; Baba, Junpei; Aoe, Shimpei; Shimada, Atsuhiro; Yamashita, Eiki; Kang, Jiyoung; Tateno, Masaru; Yoshikawa, Shinya; Tsukihara, Tomitake
Abstract: Mitochondrial cytochrome c oxidase (C c O) transfers electrons from cytochrome c (Cyt. c ) to O2 to generate H2 O, a process coupled to proton pumping. To elucidate the mechanism of electron transfer, we determined the structure of the mammalian Cyt. c –C c O complex at 2.0‐Å resolution and identified an electron transfer pathway from Cyt. c to C c O. The specific interaction between Cyt. c and C c O is stabilized by a few electrostatic interactions between side chains within a small contact surface area. Between the two proteins are three water layers with a long inter‐molecular span, one of which lies between the other two layers without significant direct interaction with either protein. Cyt. c undergoes large structural fluctuations, using the interacting regions with C c O as a fulcrum. These features of the protein–protein interaction at the docking interface represent the first known example of a new class of protein–protein interaction, which we term "soft and specific". This interaction is likely to contribute to the rapid association/dissociation of the Cyt. c –C c O complex, which facilitates the sequential supply of four electrons for the O2 reduction reaction. Synopsis: A 2.0‐Å X‐ray structure of the cytochrome c –C c O complex delineates the path for electron transfer and reveals a novel protein–protein interaction where both Cyt. c and C c O preserve their surface waters upon complex formation. The crystal structure of the mammalian Cyt. c –C c O complex is presented at 2.0 Å resolution. The specific interaction between Cyt. c and C c O is stabilized by a few electrostatic interactions between long side chains within a small contact surface. In contrast to other Cyt. c complexes, numerous water molecules are found in the long inter‐molecular span between Cyt. c and C c O. This new interaction mode likely contributes to the rapid association/dissociation of the Cyt. c –C c O complex. Abstract : The Cyt. c –C c O crystal structure delineates the path for electron transfer and illustrates a new mode of transient protein–protein interaction via ordered water molecules.